Paraoxonase 1 (PON1) attenuates sperm hyperactivity and spontaneous acrosome reaction. (17th September 2018) - Efrat, M.; Stein, A.; Pinkas, H.; Breitbart, H.; Unger, R.; Birk, R.
Abstract: Background: Sperm capacitation is essential for proper fertilization and is associated with increased sperm hyperactivity (HA) and acrosome reaction (AR). For successful fertilization, AR timing is critical; accordingly, early spontaneous AR may not facilitate fertilization. Paraoxonase 1 (PON1) possesses antioxidant properties which affect sperm capacitation. The association between PON1, semen parameters, and capacitation is not fully understood. Objective: To study PON1 activity in relation to human sperm hyperactivity and AR. Materials and Methods: Semen samples were collected, and parameters were determined (volume, concentration, total sperm count, percentage total motility, and percentage normal morphology) according to World Health Organization (WHO) guidelines. AR and hyperactivity were evaluated using FITC‐PSA, staining, and computer‐aided sperm analysis (CASA). PON1 activity was assessed using arylesterase activity assay. Results: Purified PON1 inhibited both sperm hyperactivity and AR in a dose‐dependent manner. Native semen PON1 activity was positively associated with higher sperm concentration and negatively associated with spontaneous acrosome reaction (sAR). Discussion and conclusion: PON1 may have a positive effect on fertility via its ability to prevent early spontaneous sperm capacitation and AR before reaching the female genital tract.